QUANTIFICATION OF PHENOLIC COMPOUNDS, IN VITRO ANTIOXIDANT ANALYSIS AND SCREENING OF CHEMICAL COMPOUNDS USING GC-MS IN ACALYPHA ALNIFOLIA KLEIN EX WILLD. - A LEAFY VEGETABLE - REVATHI P,; PARIMELAZHAGAN .T,; MANIAN. S, (International Journal of Pharma and Bio Sciences, 2013)
Revealing antioxidant potential of Acalypha alnifolia leaf extracts and quantification of its phenolic compounds are the main objectives. Preliminary phytochemical analysis has been carried out by using standard methods. Exemplary reducing and radical scavenging antioxidant activity have drawn closer and taken notice by in vitro assays such as FRAP, Phosphomolybdenum reducing power assays, DPPH, Superoxide and ABTS radical scavenging assays. GCMS have been undertaken for screening compounds. Quantification of phenolic compounds shows acetone leaf extract having much more than other solvent extracts. The results show acetone and methanol leaf extracts having commendable antioxidant activity than other extracts. Nine different compounds were identified from the acetone extracts when taken for GCMS. As per the previous reports, few of them possessing pharmacological importance are tabulated. This study winds up the antioxidant potency of this leafy vegetable revealing the presence of pharmacologically important compounds make them considerable for health supplements.